A contribution to the empirics of convergence in real GDP growth: the role of financial crises and exchange-rate regimes. Issue 23 (14th May 2016) - Morales-Zumaquero, Amalia; Sosvilla-Rivero, Simón
ABSTRACT: This paper investigates the convergence in real gross domestic product growth focusing on the impact of financial crises (i.e. banking crises, currency crises and debt crises) and nominal exchange-rate regimes (i.e. fixed, intermediate and flexible) on convergence. To that end, we compute four convergence indicators ( σ -convergence, γ -convergence, absolute β -convergence and conditional β -convergence) for 163 countries classified into four income groups during the period 1970–2011. The results suggest that (i) there is evidence in favour of σ -convergence and γ -convergence only for high-income countries; (ii) absolute and conditional β -convergence are present in each of the four income groups of the countries under study; (iii) exchange-rate regimes seem to play some role in upper-middle and lower-middle-income countries; and (iv) financial crises have a negative and significant impact on GDP growth independently of the income level of the countries.